Study of Preparation Sorghum Flour and Application for Analogues Rice Production - Budijanto, Slamet; yuliyanti, Yuliyanti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Sorghum (Sorghum bicolor L. Moench) is one of cerealia that high carbohydrate and protein sources. This research is aimed to obtain effect of conditioning to yield sorghum flour and sorghum varieties toward characterization of analogues rice based on organoleptic analysis. Analogues rice was produced by twin screw extruder. Conditioning process is done by added water such as 0, 10, 15, 20, and 25% from sorghum’s mass. Sorghum varieties that are used in this study are Pahat, B100, Numbu, and Genjah. All product was selected by sensory analysis. The highest yield of sorgum flour was obtained from additional of 25% water before milling process. The result of sensory analysis showed that sorghum varieties was significant effect to rice analogues. Rice analogues from Pahat and Numbu sorghum has higher consumer acceptance. Carbohydrate content of analogues rice F1 and F3 are 91.58% and 92.40%. Total dietary fiber of analogues rice F1 and F3 are 4.02% and 3.65%.Keywords: diversification, healthy rice, carbohydrate sources